Determinan Kepuasan Pengguna POEMS sebagai Trading Saham Online pada KSPM UNHI Denpasar - I Komang Arta Wiguna; I Wayan Sudiana; Ni Made Wisni Arie Pramuki (Hita Akuntansi dan Keuangan, 2023)
This research aims to examine the determinants of user satisfaction of the POEMS application with the perspective TAM theory in the Capital Market Study Group (KSPM) at the Indonmesian Hindu University Denpasar. This study use members of the UNHI Capital Market Study Group (KSPM) as population. This study use probability sampling with saturated sample technique totaling 71 respondents. SEM-PLS is technique of data analys that used in this research. The results of this research state that perceived ease of use, perceived usefulness, intention to use POEMS, and actual system use of POEMS are determinants of POEMS’s user satisfaction and self-efficacy of POEMS as an antecedent of POEMS’s user satisfaction.